A SYSTEMATIC LITERATURE REVIEW OF THE DIMENSIONS OF DIGITAL LEADERSHIP THAT AFFECT TEAM PERFORMANCE - Ratbyansa Nur; Agung Surya Dwianto (PT. Jurnal Center Indonesia Publisher, 2026)
Amidst a digitized business landscape, Digital Leadership (DL) has emerged as a crucial predictor of Team Performance. However, a fundamental question arises: which dimensions of digital leadership truly drive performance technical skills (tech-savviness), strategic vision, or relational skills? This study uses a Systematic Literature Review (SLR) of 51 articles to deconstruct digital leadership into four main dimensions: (1) Technological, (2) Visionary-Strategic, (3) Relational-Emotional, and (4) Structural-Managerial. The findings reveal an unexpected pattern: the technological dimension only acts as a hygiene factor, while the structural-managerial and visionary-strategic dimensions show the most consistent impact on team performance. Furthermore, the effectiveness of the relational dimension is highly context-dependent, strong in small Agile teams but NOT significant in large bureaucratic organizations. These findings suggest a reframing of the conventional assumption that “digital leaders” must start with technical expertise, and instead suggest that organizations should train digital talent in soft skills and strategic vision, or train existing visionary leaders in basic digital literacy.